Influence of cation building blocks of metal hydroxide precipitates on their adsorption and desorption capacity for phosphate in wastewater-A screening study - Drenkova-Tuhtan, Asya; Schneider, Michael; Mandel, Karl; Meyer, Carsten; Gellermann, Carsten; Sextl, Gerhard; Steinmetz, Heidrun (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2016)
Thirteen metal hydroxide adsorbers were synthesized via precipitation by systematically varying different two-, three- and four-valent metal precursors, namely Mg2+, Ca2+, Zn2+, Fe3+, Al3+ and Zr4+. The resulting materials were classified in four groups based on their structure, morphology and BET surface area. Two of the groups could be classified as layered double hydroxides (LDH). The rest of the materials could be either only partially related to a LDH-like structure or formed non-layered precipitates. The phosphate removal performance of each adsorber (dose 200mg/L) was tested in spiked distilled water and municipal wastewater (10mgP/L) at pH 7-8. The phosphate adsorption capacity of the materials after 1h varied between 32mgP/g (for a rod-like-sample, lacking a layered structure) and 51mgP/g (for a sample appearing as a mixture of particulate matter covered with a web-like structure). Longer contact time (24h) did not increase significantly the adsorption efficiency. None of the materials was ideally selective for phosphate, especially the ones with a clear LDH structure and highest surface area (110m2/g) which adsorbed up to 25mg/g Cl- and other competing anions. The adsorbed phosphate could be desorbed (>90% in most of the cases) by treatment with an alkaline solution (0.5M NaOH or 1M NaOH+1M NaCl) which turned out to be the best option for regeneration among many other tested combinations.
CRIS-Team Scopus Importer:2020-04-02
Keywords: Adsorbers; Layered double hydroxides (LDH); Metal hydroxide precipitates; Municipal wastewater; Phosphate recovery; Sorption